Influence of B2O3 on electrical properties and phase transition of lead-free Ba(Ti0.9Sn0.1)O3 ceramics - N. Tawichai (2018)
The phase transition and electrical properties of Ba(Ti0.9Sn0.1)O3ceramics with B2O3aded were investigated to explore the effect of B2O3addition on enhanced densification and dielectric constant of these ceramics. With increasing B2O3content, a linear reduction of ferroelectric to paraelectric transition temperature was observed. In addition, higher B2O3concentraions enhanced a ferroelectric relaxor behavior in the ceramic. Changes in this behavior were related to densification, second-phase formation and compositional variation of the ceramics.